2018
DOI: 10.3389/fimmu.2018.00460
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Generating Diverse Antibody Repertoires Using Transgenic Animals Expressing Human Antibodies

Abstract: Therapeutic molecules derived from antibodies have become a dominant class of drugs used to treat human disease. Increasingly, therapeutic antibodies are discovered using transgenic animal systems that have been engineered to express human antibodies. While the engineering details differ, these platforms share the ability to raise an immune response that is comprised of antibodies with fully human idiotypes. Although the predominant transgenic host species has been mouse, the genomes of rats, rabbits, chickens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 103 publications
0
22
0
Order By: Relevance
“…A cocktail of two antibodies, REGN10933 and REGN10987, is currently in clinical trials for treating hospitalized ( NCT04426695 ) or ambulatory ( NCT04425629 ) adult patients. Other humanized mouse technologies for isolation of monoclonal exist, and a review of different monoclonal antibodies isolated with these platforms can be found elsewhere [ 121 ].…”
Section: Mab Against Sars-cov-2mentioning
confidence: 99%
“…A cocktail of two antibodies, REGN10933 and REGN10987, is currently in clinical trials for treating hospitalized ( NCT04426695 ) or ambulatory ( NCT04425629 ) adult patients. Other humanized mouse technologies for isolation of monoclonal exist, and a review of different monoclonal antibodies isolated with these platforms can be found elsewhere [ 121 ].…”
Section: Mab Against Sars-cov-2mentioning
confidence: 99%
“…However, despite the numerous accounts of the successful use of novel immunization strategies reported by different antivenom research laboratories, very few of these strategies have found their way to the industrial setting. In the future, the possibility also exists that a combination of innovative immunization strategies with transgenic animals expressing the human antibody repertoire [ 228 , 229 , 230 , 231 ] could be employed in antivenom manufacture. This may not improve efficacy or affordability, however, it may indeed provide safer antivenoms, as the therapeutic antibodies would be of human, rather than animal origin.…”
Section: Discussionmentioning
confidence: 99%
“…Humanization of these antibodies can have great potential for biopharmaceutical development [86,87]. The recent development of transgenic chicken with human immunoglobulin loci has expedited the use of transgenic chicken derived mAbs directly for human therapeutic use [88,89]. These engineered transgenic chickens express antibodies from immunoglobulin heavy and light chain loci containing human variable regions and exhibit normal B cell development raising immune responses to conserved human targets that are non-immunogenic in mice [90].…”
Section: Chickenmentioning
confidence: 99%